SINERGITAS KELEMBAGAAN PEMERINTAH DALAM PENCEGAHAN PEREDARAN NARKOTIKA DI KABUPATEN KARIMUN TAHUN 2017-2019 - King Sing; Tito Handoko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The synergy of government institutions in the prevention of narcotics circulation is the cooperation of a relationship and order of institutions or agencies with a certain division of tasks to produce a better and greater purpose than the institution or agency itself, through communication and coordination. The formulation of the problem in this study is how the synergy of government institutions in the prevention of narcotics circulation in Karimun District in 2017-2019 and what are the factors inhibiting the institutional synergy of the government in the prevention of narcotics circulation in Karimun District in 2017-2019.             The result of this study is that first, the synergy of government institutions in the prevention of narcotics circulation conducted by government agencies in synergy is quite a lot such as, drafting policy formulation on P4GN, Implementing technical guidance in the field of P4GN to organizations in karimun district such as, anti-drug volunteers, as well as community leaders and youths in karimun district, carrying out investigations and investigations into drug abuse and trafficking , Conducting termination of organized crime networks in the field of P4GN. Second, factors that hinder the prevention of narcotics circulation in Karimun Regency are also many such as, communication factors (obstacles to investigators and investigations), as well as coordination factors (limitations of facilities and infrastructure). Keywords: Synergy, Government Institutions, Prevention of Narcotics Circulation